Hepatopulmonary shunting after surgical, interventional and systemic therapy in patients with liver malignancies scheduled for radioembolization. (August 2016) - Erxleben, Christoph; Scheurig-Münkler, Christian; Geisel, Dominik; Hamm, Bernd; Gebauer, Bernhard; Powerski, Maciej Janusz
Background: Hepatopulmonary shunts (HPS) lead to radiation exposure of the lungs in patients undergoing radioembolization (RE) of malignant liver tumors. Purpose: To retrospectively analyze how HPS is affected by prior systemic or local therapy of the liver. Material and Methods: The percentage HPS was calculated from SPECT/CT scans obtained after technetium-99 m macroaggregated albumin administration into hepatic arteries in 316 patients evaluated for RE. Results: Patients with partial liver resection ( n  = 80) did not differ in HPS from the remaining patient population ( n  = 236) (HPS (median [range]) = 10.2 [2.1–48.3]resection % vs. 8.9 [2.3–32.9]no resection %; P  = 0.527). In patients undergoing sequential RE, HPS was significantly higher in the liver lobe treated second ( n  = 10; HPS = 6.4 [2.1–10.2]firstlobe/session % vs. 12.0 [2.0–24.6]second lobe/session %; P  = 0.019). (Chemo-)embolization ( n  = 19; HPS = 11.0 [2.8–48.3]%) or transcutaneous ablation ( n  = 63; HPS = 8.8 [3.0–32.9]%) had no effect on HPS compared to patients without prior interventions (no (chemo-)embolization: n  = 297; HPS = 9.3 [2.1–47.3]%; P  = 0.489; no ablation: n  = 253; HPS = 9.5 [2.1–48.3]%; P  = 0.382). Pretreatment with sorafenib (HPS = 9.5 [2.3–35.9]yes % vs. 10.2 [2.8–42.0]no %; P  = 0.777) orbevacizumab (HPS = 10.7 [2.1–30.6]yes % vs. 9.0 [3.9–23.3]no %; P  = 0.870) had no effect on HPS. Conclusion: Sequential RE results in an increase in the HPS in the contralateral liver lobe at the time of the second RE session. Other investigated therapy do not affect HPS.